2012
DOI: 10.1016/j.rser.2012.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Review of offshore energy in Malaysia and floating Spar platform for sustainable exploration

Abstract: Rapidly rising trends of fuel consumption indicate enormous energy crisis of global proportions in near future. Following the trend, Malaysia's fuel consumption has been increasing by an annual rate of 7.2% since 1990 and has even reached 44.9 Mtoe in 2008. It is forecasted to reach 207.3 Mtoe by the year 2030. Due to serious depletion of reserves in various onshore locations, the exploration process is expanded to offshore deeper waters. Seven sedimentary basins belonging to Malaysia, in South China Sea, show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 86 publications
0
12
0
Order By: Relevance
“…Lately, the focus of wind power developers and energy planners has shifted towards the coastal zone in an increasing number of countries such as Denmark, UK, Germany and etc (Ladenburg, 2009). Many works performed in the feasibility study of OWF installation in various countries with related their criteria (Pantaleo et al, 2005;Manwell et al, 2007;Schillings et al, 2012;O'Keeffe and Haggett, 2012;Wieczorek et al, 2013;SalcedoSanz et al, 2013;Reubens et al, 2014;Martín Mederos et al, 2011;Veigas and Iglesias, 2013;Da et al, 2011;Chen, 2011;Zhixin et al, 2009;Madariaga et al, 2012;Mostafaeipour, 2010;Oh et al, 2012;Lee et al, 2013;Islam et al, 2012;Mani and Dhingra, 2013). The feasibility of wind power development depends on multi criteria like; wind resources and, especially, constructability offshore.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, the focus of wind power developers and energy planners has shifted towards the coastal zone in an increasing number of countries such as Denmark, UK, Germany and etc (Ladenburg, 2009). Many works performed in the feasibility study of OWF installation in various countries with related their criteria (Pantaleo et al, 2005;Manwell et al, 2007;Schillings et al, 2012;O'Keeffe and Haggett, 2012;Wieczorek et al, 2013;SalcedoSanz et al, 2013;Reubens et al, 2014;Martín Mederos et al, 2011;Veigas and Iglesias, 2013;Da et al, 2011;Chen, 2011;Zhixin et al, 2009;Madariaga et al, 2012;Mostafaeipour, 2010;Oh et al, 2012;Lee et al, 2013;Islam et al, 2012;Mani and Dhingra, 2013). The feasibility of wind power development depends on multi criteria like; wind resources and, especially, constructability offshore.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that constructing adjacent structures with equal floor heights and separation distances reduces the effects of pounding considerably. Study on seismic separation device has also been performed by several researchers [8][9][10][11]. Kasai and Maison [12] investigated the building pounding damage during the 1989 Loma Prieta earthquake.…”
Section: Introductionmentioning
confidence: 99%
“…Jankowski [16] performed non-linear analysis for earthquake-induced pounding of two equal height structures with substantially different dynamic properties. This response analysis show that collisions have a significant influence on the behaviour of the lighter and more flexible building especially in longitudinal direction causing generous amplification of the response and lead to extensive permanent deformation due to yielding [17][18][19][20]. Associated with the possibility of seismic vulnerability, automated mitigation of responses is required to be assessed [21][22][23][24][25][26] in construction technology.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these additives introduce potentially toxic compounds into the fluids, which must be considered when the resulting wastes are managed. Due to depletion of reserves in numerous onshore locations, the exploration process in Malaysia is expanded to offshore deeper water [5]. Because of these, drilling waste from oil and gas exploration activities has led to a serious environmental issue that need to be considered and managed according to Malaysia's legislation act.…”
Section: Literature Review Oil Exploration and Production Waste Dischmentioning
confidence: 99%